Clinical Diagnosis and Treatment Analyses on Dedifferentiated Liposarcoma of the Head and Neck: A Single-Center Experience With Systematic Review of the Literature - Xinyu Li; Qian Shi; Hongzhi Ma; Ling Feng; Shizhi He; Lingwa Wang; Haiyang Li; Jugao Fang; Ru Wang (Journal of Craniofacial Surgery, 2026)
Purpose: The aim of this study was to report 2 cases of dedifferentiated liposarcoma (DDLPS) in the peripharyngeal space and review the relevant literature to summarize its clinical and histopathologic features and therapeutic approaches, especially operative selection and prognosis. Methods: A comprehensive review of the literature was performed in January 2025 to identify relevant articles using the PubMed database. Sixty patients were included in this study: 2 new cases from Beijing Tongren Hospital in 2018 and 2023, and 58 previously reported cases that occurred between 1979 and 2024 from a systematic review of the literature. We analyzed and summarized the patients’ epidemiological data, clinical features, and treatment regimens. The main outcomes were overall survival (OS) and recurrence-free survival (RFS). Results: DDLPS was approximately twice as common in men as in women, with a median age of 61 years (range: 20–86 y). MDM2 amplification was positive in 13 patients (13/14, 92.9%). Nearly all the patients underwent surgical excision (35/36, 97.2%). Almost half of the patients (17/36, 47.2%) underwent surgery with postoperative radiotherapy (RT). The 1-year, 3-year, and 5-year OS rates were 91.3%, 81.2%, and 81.2%, respectively. The 1-year, 3-year, and 5-year RFS rates were 91.3%, 74.9%, and 64.2%, respectively. Local radical excision is the preferred treatment modality for DDLPS. Adjuvant chemoradiotherapy after radical surgery resection had no statistically significant impact on OS or RFS ( P ˃0.05). Conclusions: Detection of MDM2 during initial biopsy can prevent delays in diagnosis and treatment. Local radical excision is the preferred treatment modality for DDLPS.